Work-life balance and job satisfaction among faculty members of management campuses of the Kathmandu Valley - Neupane, Krishna Prasad (Journal of Emerging Management Studies, 2023)
Purpose - This study intends to investigate the connection between work-life balance and job satisfaction among faculty members of management campuses in the Kathmandu Valley. When companies show concern for the satisfaction of employees’ personal lives and jobs, these employees often give back by contributing to the achievement of the organization’s objectives through enhanced performance and higher staff retention.Study design/methodology/approach - A quantitative approach was adopted and a descriptive and causal-comparative research design to measure the status of work-life balance and its connection with job happiness among the faculty members of management campuses in Kathmandu. Data were collected using a structured questionnaire from 147 faculty members, and analyzed through Statistical Package for Social Sciences (SPSS) version 25.Findings - Results of this research exhibited a strong correlation between work-life balance and job satisfaction among faculty of management campuses in Kathmandu. The majority of faculty members of management campuses was able to manage their work-life responsibilities and expressed a moderate level of job satisfaction.Conclusion - Long hours and intense job pressure made it challenging for faculty to have a positive work-life balance, and an imbalance in these factors made them dissatisfied towards the job. Support from coworkers, flexible work hours, and family-friendly initiatives all contributed to a healthy balance between work-life, which helped faculty members feel more satisfied with their jobs.Implications - Theoretically, this study filled the gap that existed in the area of educational sectors in Nepal. The study is important for academics since it sparks ideas for additional research. Practically, the results of this research help to review the policies and strategies of the educational institutions to implement work-life balance practices which add to the job happiness of faculty and the quality and productivity of the institutions.